Statistical Identical the Change in the Economical Situation - Valkauskas, Romualdas (Ekonomika, 2003)
Economical situation is the function many of factors. To identical the change the economical situation above all the select economical statistical indices. They are economical indicators. In the analysis the change the economical situation will be time series of the simple and of the general economical indicators. The research the economical fluctuation of demand an ascertain they components. Ascertain the components can by make by orientated into type they dependence. The research the time series of gross domestic product (GDP) the Lithuania corroborated the usefulness the method of analytical form the time series by method of least squares in all stage of calculation.